Análise da marcha de indivíduos com doença de Parkinson submetidos à estimulação cerebral profunda de alta frequência do núcleo subtalâmico - Speciali, Danielli Souza (2012)
Levodopa has been shown to be efficient in treating Parkinson s disease (PD) in its initial phase. However, as the disease progresses, motor complications, such as abnormalities of the gait, are common. High frequency deep brain stimulation (DBS) of the subthalamic nucleus (STN) is one of the surgical treatment methods recommended for advanced cases. The aim of the present study was to compare the gait parameters of PD patients under the influence of dopaminergic medication and/or high frequency DBS using the Gait Deviation Index (GDI) and the Gait Profile Score (GPS). Sixteen PD patients were submitted to high frequency DBS of the STN. The gait assessments were applied using the UPDRS (Unified Parkinson s Disease Rating Scale) part III scale in three conditions: without medication and with stimulation; with medication and stimulation; with medication and without stimulation. The gait assessment was conducted using three-dimensional kinematics. The kinematic data was then used to calculate the GDI and GPS. The data were analyzed using the variance for repeated measures test (ANOVA), with the level of statistical significance set at P < 0.05. Statistically significant differences (P < 0.05) were found for the variables UPDRS, GDI, GPS and GVS (Gait Variable Score) (Hip Flx / Ext, Knee Flx / Ext) between the treatment with medication and without stimulation and the other two treatment conditions. In the comparison between treatment without medication and with stimulation and the other two treatment methods, or isolated medication compared to the other two treatment methods together, a high magnitude of effect was observed (Cohen s ¯d = 0.60 - 1.93) for the variables UPDRS, GPS and GVS (Hip and Knee), whereas a medium magnitude was found for GDI (Cohen s ¯d = 0.45) bilaterally. The results demonstrated that PD patients recorded greater scores in the UPDRS, GDI and GPS/MAP when the two treatments were applied together.